Improvement of graduate competencies in line with job market demands of the English language education program - Maryati Salmiah; Idris Sadri; Andri Wardana; Budiman Budiman; Khairul Azmi (Institute of Information Technology and Social Science (IITSS), 2025)
This research aims to analyze the efforts to improve the competencies of graduates from the English Language Education Study Program (TBI) at FITK UIN Sumatera Utara. A qualitative phenomenological approach is used to gain an in-depth understanding of the program administrators' perspectives regarding these efforts. The research findings indicate that the program has undertaken various initiatives, such as formulating a vision, mission, and objectives that are relevant to job market needs, implementing student-centered learning, and developing a curriculum that meets competency standards. Additionally, the program actively collaborates with various institutions and strives to enhance the quality of its faculty and facilities. However, several challenges remain to be addressed, such as limited resources and the dynamic nature of job market requirements. This research provides recommendations for the study program to continue conducting periodic evaluations and improvements, as well as to strengthen collaboration with various stakeholders to enhance graduate quality. It is hoped that these efforts will create graduates who are not only academically competent but also able to adapt quickly to changes in the work environment and meet the increasingly complex expectations of the industry. Consequently, the enhancement of graduate competencies will positively impact not only individuals but also the development of society and industry around them.